3x-2y+3z=-4

Simple and best practice solution for 3x-2y+3z=-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-2y+3z=-4 equation:


Simplifying
3x + -2y + 3z = -4

Solving
3x + -2y + 3z = -4

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2y' to each side of the equation.
3x + -2y + 2y + 3z = -4 + 2y

Combine like terms: -2y + 2y = 0
3x + 0 + 3z = -4 + 2y
3x + 3z = -4 + 2y

Add '-3z' to each side of the equation.
3x + 3z + -3z = -4 + 2y + -3z

Combine like terms: 3z + -3z = 0
3x + 0 = -4 + 2y + -3z
3x = -4 + 2y + -3z

Divide each side by '3'.
x = -1.333333333 + 0.6666666667y + -1z

Simplifying
x = -1.333333333 + 0.6666666667y + -1z

See similar equations:

| (4n^3-4n)+(3n^3+7n+8)= | | 2x-y+z=-1 | | 17=-2*x+3 | | 3(7z-4)= | | 25k^2+30k+9=0 | | 125*5-25+10= | | (-3b^2-7b-4)+(7b^2+2b-4)= | | 4t+5+4t-7t=6+2 | | x^2(x^4+16)-8x=0 | | -5=5x^2-25x+25 | | log(6)(5x-3)=4 | | 25+2t=5(t+10) | | 8m+m=14+5m | | 7x+6x-4x=16+2 | | 2(m-3)=2(m-2.5) | | 30*50=x | | 30x*50=x | | 51-x=36 | | 14k(8-k+h)= | | 40c+120a=500 | | 5m-2=4+m | | -x-111+10x=33 | | -5x-6y-6x+7y= | | -5x-6y-6x+7= | | (7u^3-u^2-7)+(2u^3-4u^2)= | | 18x-8=-24 | | 0.80x=94 | | -3x^2+600x-3375=0 | | .50x+3+.80=1.80 | | 3b+1+b=2b+9 | | 3(y+2)=y+14 | | -9x-101-3x=79 |

Equations solver categories